Implementasi Deep Breathing Exercise terhadap Tingkat Glukosa Darah pada Pasien Diabetes Mellitus - Sandra Pebrianti; Gusgus Ghraha Ramdhanie; Bambang Aditya Nugraha (Journal of Telenursing (JOTING), 2023)
This study aims to determine the effect of deep breathing exercises on blood glucose levels in diabetic DM patients. The method used is the narrative review, by searching for articles on the Pubmed and Google Scholar databases. The results showed that deep breathing exercises had a positive effect on blood glucose control in DM patients, increased relaxation, and reduced anxiety or stress. Increased peace helps reduce the hormone cortisol related to blood glucose levels. In conclusion, deep breathing exercises can lower blood glucose in DM patients. This therapy can be combined with other treatments, such as the spiritual aspects of marital therapy or spiritual mindfulness. Keywords: Deep Breathing Exercise, Diabetes Mellitus